2016
DOI: 10.1016/j.drugalcdep.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing and externalizing disorders as predictors of alcohol use disorder onset during three developmental periods

Abstract: Background The developmental pathways associated with an enhanced risk for future alcohol use disorders (AUDs) continue to be a topic of both interest and debate. In this research, internalizing and externalizing disorders were evaluated as prospective predictors of the index AUD episode onset, separately within three developmental periods: early-to-middle adolescence (age 13.0 to 17.9), late adolescence (18.0 to 20.9), and early adulthood (21.0 to 30.0). Methods Participants (N = 816) were initially randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 54 publications
(64 reference statements)
7
51
2
Order By: Relevance
“…Groenman and colleagues [24] found that childhood anxiety disorders did not increase the risk for later alcohol disorders. For example, there is evidence that externalizing disorders and being female are positively associated with anxiety [26,27], and externalizing disorders and being male are positively associated with alcohol use [28,29]. In a review of longitudinal studies which adjusted for co-occurring externalizing symptoms, Hussong and colleagues [25] also found no clear association between anxiety and internalizing symptoms with subsequent adolescent alcohol use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groenman and colleagues [24] found that childhood anxiety disorders did not increase the risk for later alcohol disorders. For example, there is evidence that externalizing disorders and being female are positively associated with anxiety [26,27], and externalizing disorders and being male are positively associated with alcohol use [28,29]. In a review of longitudinal studies which adjusted for co-occurring externalizing symptoms, Hussong and colleagues [25] also found no clear association between anxiety and internalizing symptoms with subsequent adolescent alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…externalizing disorders), and other factors such as gender, as these may be a source of bias. For example, there is evidence that externalizing disorders and being female are positively associated with anxiety [26,27], and externalizing disorders and being male are positively associated with alcohol use [28,29]. Therefore, if externalizing disorders and gender are not statistically adjusted for, they may cause spurious associations between anxiety and alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…to escape or avoid negative emotions [27]. The results of previous prospective studies on depression as a predictor of alcohol use/problems in early adolescence are however mixed [17], with reports of both an association [14] and no association [15], with one study even suggesting a protective effect against early alcohol use [13] which is why it has been argued that internalizing symptoms may be regarded as a protective factor at early ages before drinking becomes normative [16]. However, our finding rather supports previous reports of depression as a unique predictor for substance use and misuse, even at this young age.…”
Section: Discussionmentioning
confidence: 99%
“…During early adolescence, most longitudinal studies have emphasized the role of externalizing problems for early alcohol consumption [13,14], alcohol-related problems such as heavy drinking and being drunk [14], and for alcohol abuse and dependence [15]. Studies on internalizing symptoms have produced somewhat mixed results, with the report of an association between depression at age 11 and alcohol problems at age 14 [14], whereas other research has found no association between internalizing psychopathology and alcohol use disorder onset [15], or even suggested a protective effect against early substance use [13]. Since the use and misuse of alcohol becomes more normative with increasing age, it has been suggested that externalizing symptoms such as impulsivity and antisocial behavior may have a larger impact at early ages, whereas internalizing symptoms such as anxiety problems may be protective during these early years [16].…”
Section: Introductionmentioning
confidence: 99%
“…This earlier research suggested that, by adolescence, other lifetime psychiatric conditions usually preceded rather than followed AUDs, including anxiety and disruptive behavior disorders (Rohde et al, 1996) but not depressive disorders, which were more likely to follow AUD episodes (Rohde et al, 1991). Similarly, when diagnostic categories from prior developmental periods were evaluated, only externalizing behavior disorders (disruptive behavior and non-alcohol substance use disorders) predicted AUD onsets during later developmental periods (Farmer et al, 2016;Rohde et al, 2001). …”
mentioning
confidence: 95%